Factors correlated with running economy among elite middle- and long-distance runners - Hansen, C. E.; Stensvig, M.; Wienecke, J.; Villa, C.; Lorentzen, J.; Rasmussen, J.; Simonsen, E. B. (Physiological Reports, 2021)
Running economy (RE) at a given submaximal running velocity is defined as oxygen consumption per minute per kg body mass. We investigated RE in a group of 12 male elite runners of national class. In addition to RE at 14 and 18 km/h we measured the maximal oxygen consumption (VO2max) and anthropometric measures including the moment arm of the Achilles tendon (LAch), shank and foot volumes, and muscular fascicle lengths. A 3-D biomechanical movement analysis of treadmill running was also conducted. RE was on average 47.8 and 62.3 ml O2/ min / kg at 14 and 18 km/h. Maximal difference between the individual athletes was 21% at 18 km/h. Mechanical work rate was significantly correlated with VO2 measured in L/min at both running velocities. However, RE and relative work rate were not significantly correlated. LAch was significantly correlated with RE at 18 km/h implying that a short moment arm is advantageous regarding RE. Neither foot volume nor shank volume were significantly correlated to RE. Relative muscle fascicle length of m. soleus was significantly correlated with RE at 18 km/h. Whole body stiffness and leg stiffness were significantly correlated with LAch indicating that a short moment arm coincided with high stiffness. It is concluded that a short LAch is correlated with RE. Probably, a short LAch allows for storage of a larger amount of elastic energy in the tendon and influences the force-velocity relation toward a lower contraction velocity.